Suscetibilidade de Candida spp. resistentes e sensíveis ao fluconazol frente a óleos essenciais extraídos de condimentos - Pozzatti, Patrícia (2007)
In the present study, it was assessed antifungal activity of different essential oils obtained from plants traditionally used as condiments, against Candida isolates proven to be susceptible and resistant to the antifungal agent fluconazole. In this context, partial and total minimal concentration values, MICP e MICT, respectively, as well as minimal fungicidal concentration (MFC) of essential oils against different species of Candida were determined. In addition, it was evaluated minimal concentrations of oils that could inhibit germ tube formation by fluconazole susceptible and resistant isolates of C. albicans and C. dubliniensis. Candida species used in this study were: Candida albicans, C. dubliniensis, C. tropicalis, C. glabrata and C. krusei. The essential oils were obtained from: Cinnamomum zeylanicum Breyn (cinnamon), Lippia graveolens HBK (Mexican oregano), Ocimum basilicum L. (basil), Origanum vulgare L. (oregano), Rosmarinus officinalis L. (rosemary), Salvia officinalis L. (sage), Thymus vulgaris L. (thyme) and Zingiber sp. (ginger). The methodology used was broth microdilution, according to M27-A2 document provided by National Committee for Clinical Laboratory Standards (NCCLS, 2002). In order to assess inhibition of germ tube formation by essential oils, it was used the synthetic medium Phase M. Chemical composition of essential oils was obtained through gas chromatography-mass spectroscopy (GC-MS) and through calculation of retention index (RI). Results of antifungal activity tests were analyzed through Mann Whitney statistic test. Subsequently, it was noticed that basil, rosemary and sage essential oils did not show antifungal activity against Candida isolates on tested concentrations. However, cinnamon, Mexican oregano, oregano, thyme and ginger essential oils showed different levels of antifungal activity, being oregano oil the most potent and ginger oil the least efficient. Considering the extended spectrum of antifungal activity presented by these essential oils, it was noticed that similar concentrations could inhibit fungal growth or be fungicidal to isolates originally sensible and resistant to fluconazole. Besides, some oils also demonstrated moderate activity against Candida species which naturally show high fluconazole MICs, such as C. glabrata e C. krusei. All the essential oils inhibited germ tube formation, being oregano oil the most active and rosemary oil the least one. The majoritary constituents in the essential oils were: Z-isoeugenol (93,3%) for cinnamon; carvacrol (56,8%) and o-cymene (32,2%) for Mexican oregano; linalool (32,22%) and 1,8-cineole (23,61%) for basil; carvacrol (92,6%) for oregano; 1,8-cineole (28,59%) and camphor (26,31%) for rosemary; cis-thujone (40,61%) for sage; g-terpinene (64%) for thyme; and zingiberene (20,81%) for ginger essential oil. In conclusion, these results made possible evidencing that Candida spp isolates which are resistant to fluconazole, except for some particularities, were sensible to essential oils that demonstrated antifungal activity.